The Moderation Effect of Capital Structure on the Effect of Sales Growth on the Value of Manufacturing Companies Listed on the Indonesia Stock Exchange - Ida Ayu Surasmi; I Made Jamin Yasa (Universitas Warmadewa, 2022)
There are many indicators in determining the value of the company, one of which is sales growth. In addition to the level of sales growth, investors usually also focus their attention on the capital structure, because the value of the company can also be reflected in the company's ability to obtain funds to increase its growth. This study aims to determine the effect of sales growth on firm value, using the capital structure as measured by Debt to Asset Ratio (DAR), Debt to equity ratio (DER) and long-term debt (LtDER) as moderating variables. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2015 to 2017. The sample in this study amounted to 131 companies. The results of the t test and moderation show that growth has a significant positive effect on firm value, DAR weakens the effect of growth on firm value